Awareness and knowledge of birth defects among antenatal clinic attendees at thè University College Hospital, Ibadan, South-West, Nigeria (2021)
BACKGROUND: The burden of birth defects is disproportionately higher in developing countries. OBJECTIVES: This study assessed the knowledge of risk factors and prevention of birth defects among ante-natal clinic attendees at the University College Hospital, Ibadan, Oyo State, Nigeria. METHODS: This was a cross-sectional study among 415 mothers who presented at the antenatal clinic. A semi-structured questionnaire was used to obtain information on respondents' socio-demographic profile, pregnancy, birth history, knowledge on prevention and risk factors for birth defects. Descriptive statistics was used to present results, independent t-test and ANOVA were used to determine the factors associated with mean of overall knowledge of birth defects. Test statistics was done at a 5% level of statistical significance. RESULTS: The mean age of the women was 31.7 ± 4.8 years. Overall, 93 (22.4%) of the women were above 35 years, 118 (29.9%) were skilled workers and 343 (84,9%) had tertiary education. More than half (219, 52.8%) of the respondents had good knowledge of birth defects (56.4% bad good knowledge of prevention and 66.0% had good knowledge of risk factors). Antenatal clinic attendees in their first trimester had higher. mean overall knowledge score (8.3 4.9) compared to those in second (7.9 4.5) and third (7.9 4.9) trimesters but this was not statistically significant (p=0.873). However, respondents in skilled semi-skilled occupation (8.62) had a significantly higher mean knowledge score compared with those in unskilled occupation/ unemployed (7.33) (p=0,005), CONCLUSION: Knowledge of birth defects is relatively low among women. To reduce the occurrence and severity of birth defects, there is a need to educate mothers on the knowledge, prevention and importance of screening for birth defects.